2011
DOI: 10.5014/ajot.2011.09184
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Interventions for Shoulder Conditions: A Systematic Review

Abstract: The objectives of this systematic review were (1) to identify, evaluate, and synthesize the research literature of relevance to occupational therapy regarding interventions for work-related shoulder conditions and (2) to interpret and apply the research literature to occupational therapy. Twenty-two studies were reviewed for this study-16 of Level I evidence, 2 of Level II evidence, and 4 of Level III evidence. In this systematic review, limited evidence from Level I studies was found to support exercise for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The effect of exercise on the rehabilitation of SIS has been well studied, but the latest systematic reviews focusing on active exercise rehabilitation of SIS consistently report that most studies are of low to moderate quality [ 8 , 51 - 57 ]. This is primarily due to small sample sizes, inadequate blinding of patients and/or investigators and incomplete intervention descriptions, making it difficult to translate the results into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exercise on the rehabilitation of SIS has been well studied, but the latest systematic reviews focusing on active exercise rehabilitation of SIS consistently report that most studies are of low to moderate quality [ 8 , 51 - 57 ]. This is primarily due to small sample sizes, inadequate blinding of patients and/or investigators and incomplete intervention descriptions, making it difficult to translate the results into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2009 systematic review, it was concluded that supervised workplace exercise, using heavy resistance, had positive effects in controlling neck pain, and to a lesser extent, back pain, but no effect in reducing specific shoulder pain. 13 This is in contrast to the findings in studies of rehabilitative exercise treatment in which three reviews 1416 have reported at least limited evidence of exercise effectiveness in the treatment of subacromial impingement syndrome. Another recent review of workplace management of upper-limb MSDs 17 concluded that there is limited but high-quality evidence that multidisciplinary rehabilitation programs, including both physical (pain management, exercises, relaxation, ergonomic education) and psychosocial (cognitive behavioral, coping strategies, stress management) components, are beneficial workplace interventions for nonspecific arm pain.…”
Section: Introductionmentioning
confidence: 97%
“…Shoulder pain is one of the most common complaints of the musculoskeletal system, with a lifetime prevalence estimated between 7 and 10%, and is most frequently caused by impingement syndromes and rotator cuff tears [ 1 , 2 ]. Other causes for shoulder pain should also be considered in the differential diagnosis [ 3 ], such as osteoarthritis, nerve irritation [ 4 ], instability, Parsonage–Turner syndrome [ 5 , 6 ], tumors, and conditions of inner organs [ 7 , 8 , 9 , 10 ], rheumatic diseases [ 11 ], alterations of local blood vessels [ 12 ], trauma, and osteonecrosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%